СОВРЕМЕННЫЕ ПОДХОДЫ В ПРОБЛЕМНО- ДИАЛОГОВОМ ОБУЧЕНИИ ДЕТЕЙ ДОШКОЛЬНОГО ВОЗРАСТА С ИСПОЛЬЗОВАНИЕМ АРТ-ТЕРАПИИ - Айтпаева Алмагуль Карекбаевна (International Journal of Innovative Technologies in Social Science, 2019)
In today’s society, the priorities of education are changing. A student should have not only knowledge, skills and skills, but also be able to organize their own learning activities, have a willingness and ability to learn. Based on these goals, it is necessary to use a new organization of joint activities. In the developing educational system, a technology of problem-dialogic learning is implemented, which helps students to discover knowledge independently. The monologue is replaced by dialogue.